Miller's answer: Making, Saying, and the Impulse to Write. - Meredith, Christopher (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2011)
Starting with attempts by several authors, in particular Arthur Miller, to explain the nature of the impulse to write, this paper examines the tensions and relationships between conceptions of the act of writing as 'making' and as 'saying'. Writing conceived as craft is explored using recent ideas from sociology and neuroscientific research into how we learn to read and write. Writing as 'saying' is examined in terms of its capacity to 'bear witness' to the world and the nature of consciousness and some of the ethical implications of this. The capacity of fiction and poetry to represent consciousness is examined in terms of the interdisciplinary debate on the relationship between language and cognition.